2001
DOI: 10.1002/ccd.1205
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of stent delivery balloon diameters by manufacturers' compliance tables: A quantitative coronary analysis of Duet and NIR stent implantation

Abstract: Although manufacturers' compliance tables of stent delivery balloons indicate the diameter of the balloon at a given inflation pressure, it is unclear whether these data correlate with in vivo true intracoronary balloon diameters (TBDs). The TBDs of two new-generation balloon-expandable stent delivery systems (Duet and NIR) were measured by quantitative coronary analysis (QCA) in 100 consecutive patients. The manufacturers' stated balloon diameter (BD) of the stent delivery systems overestimated the TBD in 94%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The diameter of the stent delivery balloon during deployment will vary depending on the site at which measurements are made. Hehrlein et al 5 measured the MD of the stent delivery balloon during peak pressure, as in our study. They reported that the delivery balloon diameter of the Duet and the NIR stent delivery system were on average 14% and 18% smaller than predicted by the manufacturers.…”
Section: Discussionmentioning
confidence: 87%
“…The diameter of the stent delivery balloon during deployment will vary depending on the site at which measurements are made. Hehrlein et al 5 measured the MD of the stent delivery balloon during peak pressure, as in our study. They reported that the delivery balloon diameter of the Duet and the NIR stent delivery system were on average 14% and 18% smaller than predicted by the manufacturers.…”
Section: Discussionmentioning
confidence: 87%
“…5,6 Manufacturers have provided a compliance chart reporting the implanted stent diameter as a function of the nominal stent size and deployment pressure. Although these charts were determined from in vitro measurements typically done in water, 7 interventional cardiologists have routinely relied on these charts to optimize the stent dimensions according to stent size and inflation pressure during percutaneous procedures. We have used the ratio of the intravascular ultrasound (IVUS)-measured stent diameter and area to that predicted by the manufacturers' compliance chart as a measure of acute stent expansion, including the effect of both expansion of the stent delivery balloon and acute stent recoil.…”
mentioning
confidence: 99%
“…This group is at higher risk for restenosis and stent thrombosis19 20 and were excluded from previous analyses 1 2 4 14. We showed that there was actually less variation between the two measurement methods when final lumen diameters were <3 mm, implying that balloon compliance charts are even more reliable as a guide to non-complex stenting in smaller coronary arteries.…”
Section: Discussionmentioning
confidence: 87%
“…These charts are derived from in vitro testing in a water bath or related phantom at 37°C, as previously described 1. The accuracy of these charts based on in vitro measurements has been disputed by in vivo studies using quantitative coronary angiography (QCA) and intravascular ultrasound (IVUS) 1–4.…”
Section: Introductionmentioning
confidence: 99%